PENGGUNAAN EJAAN PADA JURNAL BUANA PENDIDIKAN, FKIP, UNIVERSITAS PGRI ADI BUANA SURABAYA: the use of spelling, writing journal, the journal of faculty - Retnosari, Ira Eko (Buana Pendidikan, 2015)
university can communicate new information, ideas, studies, and research results. This journal aims to describe the use of the spelling of Buana Pendidikan journal. This study applies a qualitative approach. The data source of this study is the spelling of Buana Pendidikan journal. The data collecting in this research is done by documentation method. The data collection techniques are (1) the journal collection, (2) copying journal, (3) reading journal, (4) marking with highlighter, (5) classification, (6) coding, and (7) making cards. The data analysis used descriptive method. The stages of data analysis process include (1) the data collection, (2) classification of data, (3) the determination of errors frequency, (4) explanation. The result of this journal which is the use of spelling that contained in Buana Pendidikan journal is good. It can be proved from the inaccuracy use of spelling that mostly are the use of comma, while other punctuations are relatively little. In addition, the other inaccuracies use of spelling are (1) writing capital letters, (2) writing italics, (3) the writing of numbers, (4) writing the word, (5) the use of dots, and (7) the use of commas. This journal is expected to give inputs to the lecturers to be able to use spelling correctly when writing a journal. In writing a journal, the use of spelling should be applied properly